2018
DOI: 10.3390/catal8110510
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Washcoat Deposition Process on High Pore Density Open Cell Foams Activation for CO Catalytic Combustion

Abstract: Spin coating was evaluated as alternative deposition technique to the commonly used dip coating procedure for washcoat deposition on high-porosity metallic substrates. By using spin coating, the washcoating of metallic open cell foams with very high pore density (i.e., 580 μm in cell diameter) was finely controlled. Catalytic performances of samples prepared with conventional dip coating and spin coating were evaluated in CO catalytic combustion in air, using palladium as active phase and cerium oxide as carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Blowing (dip-blowing) and centrifugation (spin-coating) are appropriate for complex shapes like open-cell foams, especially with a high pore density. Air jets and centrifugation complement gravitational forces to overcome capillary forces in draining liquid from the channels and cells. For instance, spin-coating controls the Pd-CeO 2 coating formation on FeCrAl open-cell foams with cell diameters down to 500 μm. The higher shear stresses induced by rotation during wet film deposition reduce clogging and increase the film homogeneity with respect to ordinary dip-coating (Figure ).…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…Blowing (dip-blowing) and centrifugation (spin-coating) are appropriate for complex shapes like open-cell foams, especially with a high pore density. Air jets and centrifugation complement gravitational forces to overcome capillary forces in draining liquid from the channels and cells. For instance, spin-coating controls the Pd-CeO 2 coating formation on FeCrAl open-cell foams with cell diameters down to 500 μm. The higher shear stresses induced by rotation during wet film deposition reduce clogging and increase the film homogeneity with respect to ordinary dip-coating (Figure ).…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…A proper slurry dispersion was achieved by means of the ball milling procedure reported in Section 2.2. Given the significant influence of the particle size distribution on the stability of powder dispersions in slurries, 42 powders were evaluated by granulometric analysis before and after the dispersion procedure. Results are presented in Figure 1, where the continuous line indicates the particle size distribution of the copper powder before ball milling (BBM) and dotted line refers to the results after ball milling (ABM).…”
Section: Resultsmentioning
confidence: 99%
“…Spin coating represents a valid alternative to blowing. While this technique is well consolidated in the field of flat surfaces functionalization (Sahu et al, 2009), only in recent years has it been technologically transferred to complex geometry supports (Zhang et al, 2012), with promising results reported both for honeycomb monoliths (Balzarotti et al, 2019b), open cell foams (Ambrosetti et al, 2018) and POCS (Balzarotti et al, 2021). Finally, slurry-based processes require a series of thermal treatment stages after wet coating deposition, in order to complete the washcoating process and to obtain the morphological and mechanical resistance properties of the final catalytic washcoat (Meille, 2006;Montebelli et al, 2014).…”
Section: Strategies For the Catalytic Activation Of Structured Supportsmentioning
confidence: 99%